2012
DOI: 10.3130/jaabe.11.169
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Thermostat/Hygrometer-Based Conventional and Artificial Neural Network-Based Predictive/Adaptive Thermal Controls in Residential Buildings

Abstract: This study aimed at testing the feasibility of employing artificial neural network (ANN)-based predictive and adaptive control logics to improve thermal comfort and energy efficiency through a decrease in overshoots and undershoots of control variables. Three control logics were developed: (1) conventional temperature/humidity control logic, (2) ANN-based temperature/humidity control logic, and (3) ANN-based Predicted Mean Vote (PMV) control logic. Performance tests were conducted in a thermal chamber for nona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that ANN-based control strategies are superior to mathematical models such as regression models or proportional-integral-derivative (PID) controllers for predicting thermal loads and controlling systems in buildings [13][14][15][16][17][18][19][20][21][22][23]. In particular, ANN-based control strategies provided more comfortable thermal conditions with respect to the air temperature, humidity and predicted mean vote (PMV), which represents the overall thermal quality [24] with reduced overcooling and overheating.…”
Section: Initial Prediction Modelmentioning
confidence: 99%
“…Previous studies have demonstrated that ANN-based control strategies are superior to mathematical models such as regression models or proportional-integral-derivative (PID) controllers for predicting thermal loads and controlling systems in buildings [13][14][15][16][17][18][19][20][21][22][23]. In particular, ANN-based control strategies provided more comfortable thermal conditions with respect to the air temperature, humidity and predicted mean vote (PMV), which represents the overall thermal quality [24] with reduced overcooling and overheating.…”
Section: Initial Prediction Modelmentioning
confidence: 99%
“…In previous studies conducted by our research team [12,[14][15][16][17], four thermal control logics were developed to create more comfortable thermal environments for residential buildings. The logics were conventional non-ANN-based temperature and humidity control, ANN-based temperature and humidity control, non-ANN-based predicted mean vote (PMV) control, and ANN-based PMV control.…”
Section: Introductionmentioning
confidence: 99%
“…reduced overcooling and overheating, and the amount of energy consumption of the heating and cooling systems was significantly reduced [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%